Framework Landscape Approach in Displacement Settings: Review and concept - Schure, J.; Gambo, J.; Sola, P.; Awono, A.; Buyinza, J.; Ndzodo, A. (CIFOR-ICRAF, 2022)
Targeting sustainable development and resilience at the landscape level is increasingly recognized as a viable way to overcome sectoral gaps and find solutions through dialogue with actors at multiple levels. The potential of landscape approaches to address competing claims from a myriad of actors, seems particularly relevant in refugee-hosting landscapes. This document presents results of a review of landscape approaches in displacement settings. The concept framework guided subsequent steps of developing Guidelines for a Landscape Approach in Displacement Settings (GLADS).